The Zeta-G Class: Some Computational and Analytical Aspects - Percontini, Ana Carla; Gomes-Silva, Frank; Cordeiro, Gauss Moutinho; Marinho, Pedro Rafael Diniz (Ciência e Natura, 2020)
We define a new class of distributions with one extra shape parameter including some special cases. We provide numerical and computational aspects of the new class. We propose functions using the R language to fit any distribution in this family to a data set. In addition, such functions are implemented efficiently using the library Rcpp that enables the incorporation of the codes C++ in R automatically. Some examples are presented for using the implemented routines in practice. We derive some mathematical properties of this class including explicit expressions for the moments, generating function and mean deviations. We discuss the estimation of the model parameters by maximum likelihood and provide an application to a real data set.